The perfect present - Hague, Michael (New York : Morrow Junior Books, 1996)
After choosing a special gift for his sweetheart, Jack chases it all the way to her house just in time for her Christmas party.
9 11 13 18 19
Keywords: Gifts -- Fiction; Christmas -- Fiction; Kangaroos -- Fiction; Toys -- Fiction; Birthdays -- Fiction